(untitled) (PIONIR: JURNAL PENDIDIKAN, 2022)
Learning media must be utilized optimally to help students achieve their learning objectives. Seeing students who are less enthusiastic in their learning process, this research attempts to develop a learning media that can enhance the learning interest of the first grade elementary school students, especially in learning Islamic religion subject. This research is a type of Research and Development or the so-called Research and Development (R&D), with a development model of Analysis, Design, Development or Production, Implementation or Delivery, and Evaluations (ADDIE). The product produced in this study is picture story book and student worksheet for the first grade students of elementary school, entitled I Love the Qur’an. The results of this study indicate that the quality of the product is included in the very feasible criteria with an average score of 4.85 for media experts and 4.132 for material experts. The developed media meets practical criteria with the average score of student response questionnaires for 5 score with a percentage of 100%. The developed media meets the effective criteria with the acquisition of an average score of student post-test results of 85.45 with the accomplishment percentage of 100%.